Performance Analysis and Hybrid Control Strategy Research of Vehicle Semi-Active Suspension for Ride Comfort and Handling Stability - Fei Wang; Hansheng Wen; Sanshan Xie (Machines)
With the advancement of vehicle electrification and intelligence, changes in powertrain system architecture and the addition of battery components have significantly deteriorated vehicle dynamics characteristics. Adjustable damping dampers improve vehicle performance by modifying suspension damping characteristics. Therefore, in this paper, a high-precision multi-dimensional vehicle performance representation model is developed, which includes the dynamics models of the steering and suspension systems and utilizes test results to reflect the constitutive properties of the complex nonlinear structures. The influence regularities of the suspension damping ratio on ride comfort and handling stability are analyzed, and a hybrid control strategy is proposed, which utilizes acceleration-driven damper–Skyhook control logic for vertical control and trigger rule-based control logic for lateral and longitudinal control. Finally, the effectiveness of the control strategy is validated through ride comfort and handling stability tests. The results show that the proposed hybrid control strategy significantly reduces vehicle body vibration acceleration and improves vehicle dynamic response during steering and acceleration/braking conditions.